Exploring Critical Factors Affecting Contractors’ Coopetition Relationship in International Construction Projects - Lili Gao; Xiaopeng Deng; Weimin Yang; Tengyuan Chang (Advances in Civil Engineering)
Coopetition is a revolutionary mindset that combines competition and cooperation. This paper aims to determine and to explore the critical factors affecting contractors’ coopetition relationship (CR) in international construction projects (ICPs). In order to improve CR between international contractors in ICPs, a comprehensive literature review was performed to identify the potential variables affecting the CR. A questionnaire survey of 151 professionals in both academia and industry, which included 53 variables, was conducted to explore the critical factors affecting international contractors’ CR in ICPs. Structural equation modeling (SEM) was employed to evaluate the multivariate interrelationships among those variables. As a result, nine underlying factors, including six internal factors and three external factors, were extracted and interpreted. The findings can help international contractors to understand more accurately how the coopetition relationship between contractors is affected and can provide a basis for follow-up research on how to evaluate the coopetition status of contractors and the coopetition strategies adopted in ICPs.